EOLP-02. THE EFFECT OF CLINICAL TRIAL ENROLLMENT ON SPECIALTY PALLIATIVE CARE RECEIPT IN PEDIATRIC AND YOUNG ADULT PATIENTS WITH HIGH GRADE GLIOMAS. (14th November 2022) - Roberts, Holly; Franson, Andrea; Wang, Yujie
Abstract: BACKGROUND: Palliative care has been shown to provide numerous benefits to children with cancer. Pediatric patients with high grade glioma (HGG) are particularly well suited for early involvement of palliative care given their high symptom burden and relatively poor prognosis. However, a recent study revealed that pediatric patients with primary central nervous system malignancies missed multiple opportunities for appropriate palliative care involvement. We hypothesize that clinical trial enrollment may adversely impact palliative care involvement for children and young adults with HGG. METHODS: We identified a cohort of 43 deceased patients with HGG treated at our institution. IRB exemption was obtained. For each patient, the electronic medical record was reviewed to collect demographic, diagnostic, clinical trial, treatment, and palliative care information. Statistical analysis was performed, employing Fisher exact and t tests. RESULTS: Overall, 72% (31/43) of patients had at least one visit with a specialty palliative care provider. 56% (24/43) of patients enrolled in a clinical trial with HGG-directed therapy, with 71% (17/24) of patients who enrolled in a clinical trial receiving specialty palliative care compared to 74% (14/19) of patients who were not on a trial (p = 1.000). Among patients who received palliative care, there was no statistically significant difference in the timing of palliative care involvement, measured from the date of first palliative care contact to date of death, for patients who enrolled in a clinical trial (mean = 177 days) compared to those who did not (mean = 113 days, p = 0.180). CONCLUSIONS: As our understanding of the genomic landscape of pediatric brain tumors increases, it can be expected that patients electing to enroll in targeted therapy clinical trials will also increase. As such, it is reassuring that our data suggest trial participation does not adversely impact the receipt of palliative care in children with HGG.